2016
DOI: 10.1111/jfq.12204
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Pathogens Isolated from Mussels Perna Perna Collected in Rocky Shore and Fishmarket of Niterói, RJ, and Their Respective Resistance Profile to Antimicrobial Drugs

Abstract: To assess bacteriological safety of mussels Perna perna, harvested in Itaipu, Niter oi, RJ and purchased at São Pedro fishmarket at the same city, fecal coliform counts and detection of Escherichia coli, Salmonella spp. and Vibrio spp. was performed in 27 mussel and 9 seawater samples collected between March 2012 and April of 2013. The pathogens isolated were submitted to antimicrobial susceptibility test.The majority (74%) of the mussel samples were unfit for human consumption and 89% of the seawater samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
2
0
0
Order By: Relevance
“…Data obtained showed that the levels of FIB were alarmingly higher in P. perna than in the surrounding seawaters during all the study period. These outcomes are consistent with those reported in other coastal regions worldwide, suggesting that this strong accumulation capacity is mainly related to the filter-feeding behavior of these sentinel organisms, which make them one of the best bio-indicators of fecal pollution in coastal waters (Stabili et al 2005;Martinez and Oliveira 2010;Jayme et al 2016;Bozcal and Dagdeviren 2020). Furthermore, the levels of intestinal indicators in all sampling sites were well above the permissible limits recommended according to Regulation (854/2004/EC) of 29 April 2014 for human consumption, which recommends less than 230 E. coli/100g.…”
Section: Discussionsupporting
confidence: 89%
“…Data obtained showed that the levels of FIB were alarmingly higher in P. perna than in the surrounding seawaters during all the study period. These outcomes are consistent with those reported in other coastal regions worldwide, suggesting that this strong accumulation capacity is mainly related to the filter-feeding behavior of these sentinel organisms, which make them one of the best bio-indicators of fecal pollution in coastal waters (Stabili et al 2005;Martinez and Oliveira 2010;Jayme et al 2016;Bozcal and Dagdeviren 2020). Furthermore, the levels of intestinal indicators in all sampling sites were well above the permissible limits recommended according to Regulation (854/2004/EC) of 29 April 2014 for human consumption, which recommends less than 230 E. coli/100g.…”
Section: Discussionsupporting
confidence: 89%
“…However, β-lactam antibiotics are commonly reported in aquatic environments mainly due to wastewater, sewage, and farm discharges as common contamination sources [44]. This contributes to the detection of isolates of E. coli resistant to β-lactams, which have been widely reported in Brazil, such as in aquatic environments [45,46], sea fishes [47], bivalves [48][49][50], and shrimp [51], highlighting the potential risks to public health, as shown by our data.…”
Section: Discussionsupporting
confidence: 69%